Guidelines on improving health care quality in transplantation services in the federal subjects of Russia - S. V. Gautier; S. M. Khomyakov (Вестник трансплантологии и искусственных органов, 2020)
Objective: to provide guidelines on how to improve the quality of health care in transplantation services for Russian regions; the recommendations were prepared by the Shumakov National Medical Research Center of Transplantology and Artificial Organs (Shumakov Center) based on field trips made by Shumakov Center from 2018 to 2019 in order to assess the status and development prospects of organ donation and organ transplantation in various regions of the Russian Federation. Materials and methods. Based on the over 40 field trips made by the Center, analytical reports, as well as recommendations were prepared by the Ministry of Health of Russia for regional health authorities and transplant centers. Guidelines were selected from these recommendations to address the most significant and common gaps and errors inherent in organ donation and organ transplantation in the regions. On the basis of the analytical reports, guidelines for the roadmap (plan) for organ donation and transplantation in the region were prepared. Results. A methodological framework for solving a wide range of managerial challenges on organ donation and organ transplantation is proposed for heads and experts at healthcare institutions and medical organizations. Conclusion. Organ donation and organ transplantation should be developed for the regions using the roadmap (plan) prepared and approved by the regional health authority. This approach brings stability and consistency to the development process, creates a resource base for development, and provides coordination and oversight.